1970
DOI: 10.1680/macr.1970.22.70.37
|View full text |Cite
|
Sign up to set email alerts
|

Creep and creep recovery of plain concrete as influenced by moisture conditions and associated variables

Abstract: Synopsis Experiments designed to investigate the effects of moisture content, condition of the cement gel, time of loading and time of unloading upon the creep and creep recovery of sealed and unsealed concrete specimens are described. Comparisons are made between the creep and creep recovery responses of specimens sealed immediately after curing and of unsealed specimens. The results of the experiments carried out on the drying (unsealed) specimens were easily predictable by existing theory. However, the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This idea was also followed in 1964 by Ali and Kesler using the degree of hydration as a fundamental parameter [22]. In 1970 Meyers and Slate concluded that the degree of hydration at the time of loading and the amount of microcracking developed before and during the time under load are two of the most important variables affecting the creep of concrete [20]. In 1971 Timusk and Ghosh prudently concluded that the maturing component of creep appears to arise primarily from hydration process [26].…”
Section: Fundamental Parametersmentioning
confidence: 99%
“…This idea was also followed in 1964 by Ali and Kesler using the degree of hydration as a fundamental parameter [22]. In 1970 Meyers and Slate concluded that the degree of hydration at the time of loading and the amount of microcracking developed before and during the time under load are two of the most important variables affecting the creep of concrete [20]. In 1971 Timusk and Ghosh prudently concluded that the maturing component of creep appears to arise primarily from hydration process [26].…”
Section: Fundamental Parametersmentioning
confidence: 99%
“…Despite devoted efforts to investigate the mechanisms behind shrinkage, no unified theory has been derived to explain the creep and irreversible components of desiccation shrinkage. It is generally believed that microstructural and chemical changes are the origin of these irreversible deformations, and many theories regarding these changes have been proposed, such as the formation of bonds between pressed surfaces [6], further formation of hydration products [10], creation of new interlayer space [5] and dissolution of adsorbent molecules [11]. The major components that are generally attributed as responsible for the irreversible strains are the amorphous calcium silicate hydrate (C-S-H) [3,12,13] and distributed pores inside cement paste [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was well known that creep can be influenced by many factors, such as humidity, temperature, effects of admixtures, the properties of aggregates, the stress/ strength ratio, water/cement ratio, the size of concrete, properties of cement, etc. (Gvozdev, 1966;Hummel, 1959;Kordina, 1960;L'Hermite, 1959;Meyers & Slate, 1970;Nasser & Neville, 1967;Neville & Brook, 1983;Neville & Brooks, 1987;Neville, Staunton, & Bonn, 1966;Raina, 1989;Troxell, Raphael, & Davis, 1958;Wanger, 1958). Besides, shrinkage is another behavior of concrete, which reduces the strength.…”
Section: Introductionmentioning
confidence: 99%